Clinical features and outcome of multisystem inflammatory syndrome in children (MIS-C) patients in northwest general hospital and research center Peshawar - Rehman, Fatima; Sethi, Bilal; Iqbal, Sahar; Noreen, Saima; Hussain, Saba; Rehman, Aziz Ur (International Journal of Pathology, 2025)
Background: Multisystem Inflammatory Syndrome in Children (MIS-C) is a post–COVID-19 hyperinflammatory condition with multisystem involvement. Due to limited regional data, this study assessed the clinical features and outcomes of MIS-C in children admitted to Northwest General Hospital, Peshawar.Methods: A six-month descriptive cross-sectional study was conducted after ethical approval. Seventy-nine patients aged 0–19 years meeting WHO/CDC MIS-C criteria were included through sequential sampling. Clinical presentation, laboratory findings, treatment, and outcomes were recorded and analyzed using SPSS 23. Results were reported as frequencies, percentages, and means where appropriate.Results: Most patients were 6–12 years old (44.3%) and female (63.3%). Prior COVID-19 exposure was documented in 69.6%, and 72.2% had elevated antibody titers. Common symptoms were reduced oral intake (59.5%), rash (45.6%), conjunctival congestion (40.5%), vomiting (40.5%), abdominal pain (29.1%), hypotension (35.4%), and tachycardia (32.9%). CRP (74.7%), ESR (49.4%), and AST (51.9%) were the most frequently elevated markers. Cardiac dysfunction occurred in 7.6% of cases. Intravenous immunoglobulins (IVIG, 94.9%) and steroids (72.2%) were the main treatments; 36.7% required inotropes and 3.8% mechanical ventilation. Mortality was 21.5%, significantly higher among those with concurrent measles.Conclusion: MIS-C commonly involved gastrointestinal, cardiovascular, and mucocutaneous systems. Most children improved with timely Intravenous immunoglobulins, steroid therapy, and supportive care, but coexisting measles was associated with markedly poorer outcomes